Технологія кранового монтажу покрівель із легких металевих конструкцій - Квітченко, М. І.; Чебанов, Т. Л. (Ways to Improve Construction Efficiency, 2014)
Article deals with the installation of roofs made of lightweight metal. Method of mounting large-block constructions production facilities is especially important for large-scale construction on the area, volume and weight of the industrial facilities. From finding the rational design and technological solutions assembling the authors performed a patent search . The existing links to local inventors , inventors' certificates , literature review, structured findings do allow classification of implementing these techniques in practice.